STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN PARTISIPASI MASYARAKAT MELALUI KEGIATAN SEKOLAH - Prabandari, Diah Ayu; Mustiningsih, Mustiningsih; Sobri, Ahmad Yusuf (Jurnal Visi Ilmu Pendidikan, 2025)
This research aim to principal"™s strategy in estabilishing school and community relationship  by school"™s activity. The approach in this study is a qualitative approach.  The research was conducted in  Junior High School  An  Nur Bululawang. Data collection techniques were carried out using interviews, observation and documentation. To obtain the validity of the data obtained by using source triangulation and technical triangulation. The results of this research are that there are strategic steps taken by the school principal to increase community participation, namely 1) there are several activities that involve the community, (2) several results were found from community participation, not only from the increasing number of prospective new students but also from the assistance from the community in the form of materials or energy to support the activities carried out at the school